Tourism: A Growing Industry of India - Yadav, Arvind Kumar (Journal of Commerce and Trade, 2017)
Tourism today is belived to be one of the largest industries in the world.The unmatched potential of tourism in country’s economy, contribution on lasting peace and faciliating in international brotherhood and environmental awareness have already attracted many government and nations to welcome it. There are two ways we can look at this activity. One is visiting some place for a reason and then go as a tourist or you can directly go as a tourist. You already know that tourism is an activity done by an individual or a group, moving from one place to another, from a country to another for performing a specific task, or a visit to a place or several places for entertainment which leads to an awareness of other civilizations and cultures and history. Tourism is an important industry that depends on culture and science and has a direct impact on the national revenue for all touristic countries. The World Travel and Tourism Council calculated that tourism generated 121 billion or 6.4% of the nation’s GDP in 2011. It was responsible for 39.3 million jobs, 7.9% of its total employment. The GDP of the tourism sector has expanded 229% between 1990 and 2011. The sector is predicted to grow at an average annual rate of 7.7% in the next decade. In a 2011 forecast the World Travel and Tourism Council predicted the annual growth to be 8.8% between 2011 and 2021. This gave India the fifth rank among countries with the fastest growing tourism industry.